The influence of substituents in governing the strength of the P–X bonds of substituted halophosphines R1R2P–X (X = F and Cl) - O’Reilly, Robert J.; Karton, Amir (Frontiers in Chemistry, 2023)
In this study, the gas-phase homolytic P-F and P-Cl bond dissociation energies (BDEs) of a set of thirty fluorophosphine (R 1 R 2 P-F) and thirty chlorophosphine-type (R 1 R 2 P-Cl) molecules have been obtained using the high-level W2 thermochemical protocol. For the R 1 R 2 P-F species, the P-F BDEs (at 298 K) differ by up to 117.0 kJ mol -1 , with (H3Si)2P-F having the lowest BDE (439.5 kJ mol -1 ) and F2P-F having the largest BDE (556.5 kJ mol -1 ). In the case of the chlorophosphine-type molecules, the difference in BDEs is considerably smaller (i.e., 72.6 kJ mol -1 ), with (NC)2P-Cl having the lowest P-Cl BDE (299.8 kJ mol -1 ) and (HO)2P-Cl having the largest (372.4 kJ mol -1 ). We have further analyzed the effect of substituents in governing the P-F and P-Cl BDEs by considering the effect of substituents in the parent halogenated precursors (using molecule stabilization enthalpies) and the effect of substituents in the product radicals (using radical stabilization enthalpies). Finally, we have also assessed the performance of a wide range of DFT methods for their ability to compute the gas-phase P-F and P-Cl BDEs contained in this dataset. We find that, overall, the double hybrid functional DSD-PBEB95 offers the best performance for both bond types, with mean absolute deviations of just 2.1 (P-F BDEs) and 2.2 (P-Cl BDEs) kJ mol -1 .